Public Service Innovation Strategy In Maintaining The Integrity Zone Predicate At The Banten Regional Office Of The Directorate General Of Customs And Excise - Agustina Mogi; Hadi Supratikta; Nurhadi Nurhadi (Universitas Dehasen Bengkulu, 2026)
The purpose of this study is to analyze the efforts or strategies undertaken by the Banten Regional Office of the Directorate General of Customs and Excise to sustain the development of the Integrity Zone, which has been awarded the titles of Corruption-Free Zone (WBK) and Clean and Service-Oriented Bureaucracy Zone (WBBM). The strategies analyzed include what has been done and what should be done in the management of human resources and public service innovation. The method used in this study was a descriptive qualitative approach, data collection was carried out through focus group discussion, interviews and a review of documentation. The focus group discussion was attended by members of the Integrity Zone Development Team at the Banten Regional Office, while the interviews were conducted with competent officials at Integrity Zone Development Team at Banten Regional Office of the Directorate General of Customs and Excise. The results of the study indicate that the internal conditions of the Banten Regional Office of the Directorate General of Customs and Excise are relatively strong, where strengths are more dominant than weaknesses. In addition, external conditions indicate that the Banten Regional Office of the Directorate General of Customs and Excise has greater opportunities than threats so that it is able to respond well to external opportunities. This condition reflects the commitment and efforts of all levels of the Banten Regional Office of the Directorate General of Customs and Excise to eradicate corruption and improve the quality of public services in order to maintain the WBK and WBBM Integrity Zone.